Pengaruh Subsektor Perkebunan Terhadap Pertumbuhan Ekonomi Di Kabupaten Kampar - Hira Masesy Yolanda; Suardi Tarumun; Eliza ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this study is to identify which sub sector basis in Kampar district and see a shift, competitiveness and growth profiles in the sector and sub-sector economy in Kampar district. The types of data that used are secondary data (time series) between 2002 until 2011. Secondary data obtain from relevant government agencies such as the regional gross domestic product (PDRB), the data of production area and amount of production in Kampar district. Obtained data were collected, tabulated and analyzed in with the relevant theory, such as Location Quotient (LQ) method, in LQ analysis, there are localization and specialization’s analysis., Dynamic location Quotient (DLQ), shift share analysis and area’s growth profile. The Location Quotient method was used to know is farm’s subsector is basis subsector in Kampar district, localization was used to know the level of farm’s activity distribution in Kampar district and the level of specific commodity’s distribution in Riau province. Dynamic location Quotient was used to know position changes of an economics sector in the future, analysis shift share was used to see the friction of competitiveness sector and economy subsector in Kampar district and growth area’s profile the purpose is to identify the growth of PDRB’s economy sector in Kampar district within specific time period, by expressing the percentage change in the growth component’s proportional to the share of the growth areas. Keywords: basis sector, growth of economy, competitiveness, growth profile